ASSOCIATION OF HYPERTENSIVE RETINOPATHY WITH ANGIOGRAPHIC SEVERITY OF CORONARY ARTERY DISEASE DETERMINED BY SYNTAX SCORE - Habib, Syed Abid; Jibran, Muhammad Saad; Khan, Sher Bahadar; Gul, Adnan Mehmood (Journal of Ayub Medical College Abbottabad, 2019)
Background: Hypertension is a leading cause of morbidity among developing and developed countries. Hypertensive Retinopathy is a micro vascular complication of long standing hypertension while CAD is a macro vascular complication. The main objective of the study was to determine the association between worsening grade of hypertensive retinopathy with angiographic severity of coronary artery disease (CAD) measured by Syntax Score. Methods: This was a cross sectional study which was conducted after approval from IRB. All patients with history of hypertension, who underwent coronary angiography, were included in the study. After a detailed history and physical exam, all included patients were subjected to fundoscopy. Patients were categorized into 4 groups according to Keith et al classification of hypertensive retinopathy: No HR, Mild HR, Moderate HR and Severe HR. Patients were also categorized into three groups on the basis of angiographic severity of CAD by syntax score (SS): Mild CAD (SS<22), Moderate CAD (SS: 22-32) and Severe CAD (SS>32). Data was analysed in SPSS Version 20.0. Categorical and continuous variables were described as frequencies/percentages and Mean±SD respectively. Results: A total of 370 patients were included in the study out of which 205 were males with a mean age of 55.3±10.07 years. Mean duration of hypertension was 8.1±2.7 years with a mean SBP of 130.1±37.2 mmHg and mean DBP of 90.3±17.3 mmHg. Patients with no HR, mild HR, moderate HR and severe HR had a mean SS of 11.7±4.5, 17.1±3.9, 26.3±5.1 and 37.9±5.1 respectively. Significant association was found between HR and severity of CAD with a chi square value of 285.53 (p<0.001). PORs for worsening grade of HR with severity of CAD increased from 0.341 (p<0.001) for mild HR to 2.33 (p<0.001) times for severe HR. Conclusion: A higher grade of hypertensive retinopathy is significantly associated to a higher angiographic severity of CAD by syntax score. Keywords: Coronary Artery Disease; Syntax Score; Hypertensive Retinopathy